Relatedness within and between Agta residential groups. (22nd September 2021) - Dyble, Mark; Migliano, Andrea Bamberg; Page, Abigail E.; Smith, Daniel
Abstract: Abstract: Theoretical models relating to the evolution of human behaviour usually make assumptions about the kinship structure of social groups. Since humans were hunter–gatherers for most of our evolutionary history, data on the composition of contemporary hunter–gatherer groups has long been used to inform these models. Although several papers have taken a broad view of hunter–gatherer social organisation, it is also useful to explore data from single populations in more depth. Here, we describe patterns of relatedness among the Palanan Agta, hunter–gatherers from the northern Philippines. Across 271 adults, mean relatedness to adults across the population is r = 0.01 and to adult campmates is r = 0.074, estimates that are similar to those seen in other hunter–gatherers. We also report the distribution of kin across camps, relatedness and age differences between spouses, and the degree of shared reproductive interest between camp mates, a measure that incorporates affinal kinship. For both this this measure ( s ) and standard relatedness ( r ), we see no major age or sex differences in the relatedness of adults to their campmates, conditions that may reduce the potential for conflicts of interest within social groups.